Improved removal of Congo Red from wastewater by low-rank coal using micro and nanobubbles. (1st May 2021) - He, Qiongqiong; Cui, Rong; Miao, Zhenyong; Xing, Yaowen; Wan, Keji; Gao, Mingqiang; Zhang, Mingliang
Graphical abstract: When Congo red (CR) solution passed through the micro-nano-bubble (MNBs) generator, 25% of CR molecules was are oxidized by free radicals produced by MNBs, and the other CR molecules are adsorbed on the bubbles, and then transferred to the absorbents (LRC) to accelerate the adsorption process greatly due to the high concentration and large surface area of MNBs and its nature to attached to LRC. Highlights: Micro and nanobubbles (MNBs) coupled with low-cost absorbent used for dye adsorption. Some of Congo red molecules was are oxidized by free radicals produced by MNBs. MNBs accelerated the Congo red adsorption process on low-rank coal greatly. The maximum adsorption rates with MNBs were 2 times of that without MNBs. Abstract: The influences of micro and nanobubbles (MNBs) on the adsorption of Congo Red (CR) on low-rank coal (LRC) were investigated. The size of microbubbles and nanobubbles diameters ranged from 2 to 600 μm and 50–200 nm, respectively. MNBs simultaneously increased adsorption capacity and rate of CR on LRC; the maximum adsorption rates achieved with the use of MNBs were 2 times of that without MNBs for both Wanli and Mengdong coal. Without MNBs, it took 25 min for Wanli coal to achieve the same residual CR concentration that Wanli with MNBs achieved in 1 min. The MNBs mainly reduced the CR concentration through the generation of OH radicals and improvement of its adsorption on LRC. MNBs were easy to attached to LRC particles, so they could act as "porter" to carry CR to LRC. The high concentration of CR-carrying MNBs increased CR/LRC contact probability to accelerate the adsorption of CR. The mechanism by which MNBs assisted adsorption provides a new method of removing organic pollutants in less time and with lower cost, which holds great potential in a wide range of applications.